Is there any relationship among the risks of banks in Malaysia? - Htay, Sheila Nu Nu; Salman, Syed Ahmed (IDOSI Publication, 2014)
Banking sector is the backbone of any country’s economy and involves in the risky business activity. It is also highly regulated industry mainly due its high risky activities. Among the risks faced by the banks, operating risk, liquidity risk, credit risk and market risk are the major risk. The objective of this study is to examine the correlation among these risks in the context of locally owned banks in Malaysia. The data has been collected from five listed banks for 10 years (2002-2011). Malaysian banking sector is chosen due to its unique nature of banking environment which promotes Malaysia to be the hub of Islamic banking and finance and which accommodate the dual banking system. Pearson correlation method is used to find out the relationship among the risk. The findings show that the risk relation varies across the banks and it is difficult to generalize the risk relationship nature in Malaysian banks. We suggest the banks need to manage the risks based on their risk portfolio and risk appetite. These findings contribute to enhance the knowledge on risk behaviors and will be the interest of regulators, investors and industrial players for future making rules, investment decision and plan the risk management.